Evaluating the fat distribution in idiopathic intracranial hypertension using dual-energy X-ray absorptiometry scanning - Hornby, C; Botfield, H; O'Reilly, M; Westgate, C; Mitchell, J; Mollan, S; Manolopoulos, K; Tomlinson, J; Sinclair, A (Taylor and Francis, 2017)
Idiopathic intracranial hypertension (IIH) is strongly associated with obesity. We aimed to utilise dual-energy X-ray absorptiometry (DEXA) to characterise fat distribution, and to evaluate change in fat mass and distribution following weight loss. IIH patients (n = 24) had a similar fat distribution to body mass index (BMI)- and gender-matched obese controls (n = 47). In the IIH cohort, truncal fat mass correlated with lumbar puncture pressure. Weight loss in IIH patients resulted in a significant reduction in disease activity and fat mass, predominantly from the truncal region (-4.40 ± 1.6%; p = 0.008) compared with the limbs (+0.79 ± 6.5%; p = 0.71). These results indicate that, contrary to previous studies using waist-hip ratios, IIH adiposity is centripetal, similar to simple obesity. Future studies should establish the risk of the metabolic syndrome and the role of adipose tissue depot-specific function in IIH.